The mind's eye [compact disc, unabridged] - Sacks, Oliver, 1933-2015 (Random House Audio, 2010)
Includes stories of people who are able to navigate the world and communicate with others despite losing what many of us consider indispensable senses and faculties: the power of speech, the capacity to recognize faces, the sense of three-dimensional space, the ability to read, and the sense of sight. This book is a testament to the complexity of vision and the brain and to the power of creativity and adaptation, and it provides a whole new perspective on the power of language and communication, as we try to imagine what it is to perceive through another person's eyes, or another person's mind.